Edukasi Moderasi Beragama Berbasis Positive Reinforcement di SMA Kristen 2 SoE, Kabupaten TTS - Leobisa, Jonathan; Adi Saingo, Yakobus; Damnosel Bara Pa, Hemi; Jhonnoto Dami, Friderich (LPPM Universitas HKBP Nommensen, 2025)
Educational institutions should be at the forefront in preparing every component in them to help maintain harmony between religious communities, bearing in mind that existing religious pluralism, if not managed properly, can become a suggestion of intolerance by certain elements of society. The team of lecturers and students of the Program Magister PAK – IAKN Kupang believes that there is a need for activities that can educate school components so that they can have high awareness to help maintain the culture of religious tolerance that has been maintained throughout the midst of the diverse society of SoE City, South Central Timor Regency. Therefore, PkM activities were held which aimed to strengthen the values ​​of religious tolerance with the theme of religious moderation education based on positive reinforcement at Christian High School 2 SoE, TTS Regency. The method used in implementing this PKM activity is Participatory Action Research (PAR) which is carried out by socializing the implementation of positive reinforcement-based religious moderation values ​​for 54 participants consisting of Principals, teachers, staff/employees, and students of Christian High School 2 SoE. The data collected through active discussions between IAKN Kupang lecturers and participants were then processed and analyzed reductively, thereby showing the results of PkM activities that teachers and students need to work together in implementing religious moderation values ​​such as non-violent behavior, upholding national commitments, and promoting religious tolerance. , which is stimulated/stimulated from within oneself so that each individual can naturally have a high level of awareness in carrying out these values ​​voluntarily and pleasantly as a character that is inherent in daily activities. The implementation of PkM activities by the team of lecturers and students of the Program Magister PAK – IAKN Kupang was seen as very beneficial and had a significant impact in increasing participants' awareness as measured by a satisfaction level of 3.68%.